CRUDE PROTEIN DEGRADABILITY (in sacco) OF UNTREATED AND TREATED NAPIER GRASS (Pennisetum puerperium) SILAGES - Hyelda, A.J.; Gworgwor, Z.A.; Mbaya, Y.P.; Yakubu, A.K.; Ahmed, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to determine crude protein rumen degradability of differently ensiled Napier grass, and the nylon-bag procedure was used. Napier grass harvested at 16 weeks after planting was allowed to wilt for a day before ensiling. There were four treatments thus; T1=untreated/plain, T2=treated with 4% urea, T3=treated with 4% molasses and T4=treated with 2% molasses and 2% urea. Two White Fulani bulls (weighing 285kg and 292kg), fitted with rumen cannula were used. The incubation periods were 6, 12, 24, 48, 72 and 96 hours. Representative samples of each feed material were obtained and shed-dried, ground using pestle and mortar and sieved through a 1mm sieve. Four grams each of the representative samples were weighed into the nylon bags and incubated in the rumen. The samples were prepared in triplicate for every feed material, for each animal. The results of the CP disappearance of the silages showed that T2 (4% urea treated Napier grass) had the highest rumen degradability in the earlier incubation times (22.61% after 6 hours and 28.61% after 12 hours). At 24 hours to 96 hours of incubation, T3 (4% molasses treated Napier grass) recorded the highest degradability (41.05%, 52.89%, 61.19% and 68.44% for 24, 48, 72 and 96 hours respectively). For CP kinetics of the silages, T2 had the highest soluble fraction ‘a’ (15.09%), T3 had the highest insoluble but potentially degradable fraction ‘b’ (60.11%) and potential degradability ‘a+b’ (75.11%). Outflow rate of degradation per hour ‘c’ was highest in T2 (0.091). The treated Napier grass silages have shown to have better crude protein degradability than that of the untreated/plain silage. Feeding these silages to ruminants is therefore recommended as they have recorded adequate crude protein degradability in the rumen, particularly the 4% molasses treated silage.